Conducting polymer electrodes for visual prostheses. - Green,RA; Devillaine,F; Dodds,C; Matteucci,P; Chen,S; Byrnes-Preston,P; Poole-Warren,LA; Lovell,NH; Suaning,GJ (Conference proceedings : ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Conference, 2010)
Conducting polymers (CPs) have the potential to provide superior neural interfaces to conventional metal electrodes by introducing more efficient charge transfer across the same geometric area. In this study the conducting polymer poly(ethylene dioxythiophene) (PEDOT) was coated on platinum (Pt) microelectrode arrays. The in vitro electrical characteristics were assessed during biphasic stimulation regimes applied between electrode pairs. It was demonstrated that PEDOT could reduce the potential excursion at a Pt electrode interface by an order of magnitude. The charge injection limit of PEDOT was found to be 15 x larger than Pt. Additionally, PEDOT coated electrodes were acutely implanted in the suprachoroidal space of a cat retina. It was demonstrated that PEDOT coated electrodes also had lower potential excursions in vivo and electrically evoked potentials (EEPs) could be detected within the vision cortex.